The Effect of Using Ice Breaking on Learning Motivation of Elementary School Students in Learning Science - Taupik, Riska Putri; Fitria, Yanti; Syarif , Muhammad Ilham; Amini, Risda (Indonesian Journal of Science and Education, 2023)
Low learning motivation among elementary school students remains a major challenge in science education. This study aimed to investigate the effect of using ice breaking activities on students’ learning motivation in science classes. A quasi-experimental design was employed with two groups of fifth-grade students in an elementary school in West Sumatra, Indonesia. Data were collected through questionnaires and analyzed using the Paired Sample t-test. The findings revealed that the average motivation score of the experimental group increased from 49.84 (pre-test) to 82.63 (post-test), while the control group showed a smaller improvement. The t-test result (t = 3.84, p < 0.05) indicated a significant effect of ice breaking on students’ learning motivation. These findings suggest that incorporating ice breaking techniques can enhance students’ engagement and focus during science learning, making lessons more dynamic and enjoyable. Future research may explore different types of ice breaking activities and their impact on other cognitive or affective learning outcomes.